FeII Complexes with Triple N1, N2‐Triazole Bridge Schiff Base Ligand: Antiferromagnetic Dimer vs. Spin Conversion Trimer. Issue 37 (25th September 2018) - Li, Ai‐Min; Hochdörffer, Tim; Wolny, Juliusz A.; Schünemann, Volker; Rentschler, Eva
Abstract : Based on the p ‐tolyl functionalized Schiff base 1, 2, 4‐triazole ligand 4‐( p ‐tolylidene‐amino)‐4 H ‐1, 2, 4‐triazole (toltrz), a series of three triazole‐bridged Fe II complexes have been prepared. The compounds represent a range of dinuclear and trinuclear species, with µ2 ‐ N1, N2 ‐triazole bridges linking the Fe II centers. Mössbauer spectroscopy and magnetic susceptibility measurements reveal a gradual single‐step spin crossover (SCO) behavior for the trimeric compound3 on the central Fe II site. Single‐crystal X‐ray diffraction at 120 K confirms that the central Fe II site undergoes a HS to LS transition while the peripheral Fe II remain in HS state (HS = high spin; LS = low spin). Compounds1 and2 are isostructures with different terminal ligand XCN (X = S, Se), these two compounds stay in high spin state over the whole temperature range but display weak antiferromagnetic exchange coupling. Abstract : A series of linear Fe II complexes with 4‐( p ‐tolylidene‐amino)‐4 H ‐1, 2, 4‐triazole ligand were synthesized and characterized. A gradual spin transition was found on the central Fe site of the trinuclear complex.